Hydrolysis-Driven Buoyancy Propulsion System for Submersibles - Borchsenius, Jo (Auckland University of Technology, 2011)
The research presented herein intends to improve the flexibility of underwater gliders with the development of a novel propulsion system. The proposed Chemical Buoyancy Drive is indicated to yield up to 20 times the amount of available electric energy and exhibit 90% propulsion efficiency, compared to that of the commercial underwater glider named “Spray” developed by Scripps Institution of Oceanography at a depth of 1,500 m. Its performance is readily optimised to any depth, and there is no need for a thermal incline in the operational environment. Also the need to isolate the energy storage from external pressure is eliminated by the use of lithium hydride suspended in a slurry, which is reacted with seawater to generate hydrogen. The subsequent increase in volume results in propulsion through the induced hydrodynamic forces on the hull and wings, and the hydrogen can be consumed in a fuel cell providing electric energy. A prediction of the drive’s performance up to 10,000 m depth is presented, which has been based on data from the studied literature. This has been verified through the developed experiments up to an equivalent of 3,000 m. Additionally, a study on potential improvements and the practical realisation of the system is presented. The proposed Chemical Buoyancy Drive could be a competitive alternative to the propulsion of underwater gliders and other autonomous underwater vehicles.
Keywords: Underwater glider; Hydrogen; Chemical; Hydrides; Propulsion; Fuel cell; Buoyancy; Autonomous Underwater Vehicle; Lithium; Reaction; Seawater; Solubility; Compressibility; Density; Kermadec Submersible